Trends of Using Facebook and its Impact on the Work Productivity of Lecturers at Higher Education in the City of Jambi - Samsu Samsu (IJER (Indonesian Journal of Educational Research), 2021)
This study aims to explore the information about the trend of using facebook and its impact on the work productivity of lecturers at higher education in the city of Jambi. This research was developed from various sources related to the facebook findings of Mark Elliot Zuckerberg at Harvard University since 2004. Data collection in this study was collected using the interview and literature review. Interviews were conducted directly with several sources, while literature review done through collecting journal regarding the research problems. The finding show that the lecturers from 14 higher education in the city of Jambi who have used facebook service because the reason not to say technology stutter (1.88%), spreading of issues and provocation (1.72%), looking for friends (1.43%), frank (1.30%), educational and work purposes (0.47%). This study proves that the using facebook has a contribution on the work productivity of lecturers at the fourteen higher educations in the city of Jambi.